Information Technology Utilization in The Disclosure of Drug Crimes by West Jakarta Metro Police - Satria Arya Pradana; Suryadi Suryadi; Ahwil Luthan (Ridwan Institute, 2022)
The discussion in this study is the continued increase of circulation and abuse of drugs in West Jakarta Police jurisdiction requires Police to make breakthrough efforts by utilizing Information Technology, namely by tapping the perpetrators' cell phones. Drug cases and these efforts directly impact the performance of the investigators and the number of drug cases they have successfully handled. This paper will explain: 1) Illicit trafficking and drug abuse in the Legal area of ??the West Jakarta Police has reached an alarming level because international and local trafficking syndicates prefer Jakarta as their circulation area. Data evidence this for the period 2019 and 2021 the total number of perpetrators who have been arrested will reach 1014 people; 2) Disclosure of drug cases conducted by West Jakarta Police is carried out using three methods, namely conventional methods, utilizing information technology methods, and combination methods; 3) The impact of the use of information technology in disclosing drug cases by West Jakarta Police: (a) Improving the performance of investigators' personnel; (b) Disclosure of drug cases can be optimal; (c) Drug networks will be exposed to top-level dealers.